ECtHR: Chocholáč v. Slovakia - Andrej Beleš (Bratislava Law Review, 2022)
The purpose of this commentary is primarily to analyse the judgment of the ECtHR in case of Chocholáč v. Slovakia on 7 July 2022 and the related ruling of the Constitutional Court of the Slovak Republic of 2017. In these decisions, the courts dealt with the general prohibition on the possession of pornographic materials in the serving of a prison sentence. What is interesting about these decisions are the fundamental substantive differences in terms of the assessment of the legitimacy and proportionality of that prohibition in relation to the right to privacy and the right to information of persons in the serving of a prison sentence. The practical implementation of the ECtHR decision must be seen in the context of the problems of the Slovak prison system.